Computional Fluid Dynamics Workshop, 2004 - Universiti Malaysia Sarawak, Centre for Academic Information Services (Universiti Malaysia Sarawak (UNIMAS), 2004)
Opening ceremony of Computional Fluid Dynamics Workshop by Datuk Larry Sng representing YB Tan Sri Datuk Amar Dr. George Chan Hong Nam